IMPLEMENTASI PEMBENTUKAN KARAKTER RELIGIUS MELALUI PROGRAM FULL DAY SCHOOL BAGI PESERTA DIDIK DI SDIT AL IZZAH 2 - Imam, Ahzami Khairul; Hakim, Zerri Rahman; Ngulwiyah, Istinganatul (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to describe the planning, implementation, as well as supporting and inhibiting factors in the implementation of the full-day school program at SDIT Al Izzah 2. The research employed a descriptive qualitative method, with data collected through interviews, observations, and documentation. The data were analyzed using the Miles and Huberman model. The results of the study indicate that the planning of the full-day school program at SDIT Al Izzah 2 began with the preparation of the academic calendar, classroom administration, provision of adequate facilities and infrastructure, and the development of religious habituation and self-development programs, which were carried out through extracurricular activities. The implementation of the full-day school program ran well and in a conducive manner, where students participated in classroom learning, religious habituation programs, and self-development programs through extracurricular activities. The supporting factors for the implementation of the full-day school program included a conducive environment and collaboration between parents and teachers. Meanwhile, the inhibiting factors were an unconducive environment and differing perceptions between parents and teachers.